1986
DOI: 10.1159/000242614
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Metabolism in Pregnancy, Fat Transport to the Fetus, and the Effects of Diabetes

Abstract: The objective of this paper is to review the extent and mechanisms of lipoprotein alterations in pregnancy, present new data relating to placental lipid transport in. normal humans and diabetic animals and consider possible effects on fetal growth and development in normal and diabetic pregnancy. The concentration of all lipoprotein fractions increases during pregnancy. VLDL cholesterol and triglyceride increase 2.5-fold over prepregnancy levels and LDL cholesterol increases 1.6-fold, all with peak levels at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
0
5

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(114 citation statements)
references
References 28 publications
11
98
0
5
Order By: Relevance
“…The VLDL-C level, as reported by some researchers, might rise upto 2.5 folds at term over the pre-pregnancy level (15,16). VLDL level further increase in PIH as evidenced in the present study in corroboration with those of other workers (9,10,15), perhaps due to increased VLDL lipoproteins which accumulate over the maternal vascular endothelium, particularly those of uterine and renal vessels (17).…”
Section: Resultssupporting
confidence: 90%
“…The VLDL-C level, as reported by some researchers, might rise upto 2.5 folds at term over the pre-pregnancy level (15,16). VLDL level further increase in PIH as evidenced in the present study in corroboration with those of other workers (9,10,15), perhaps due to increased VLDL lipoproteins which accumulate over the maternal vascular endothelium, particularly those of uterine and renal vessels (17).…”
Section: Resultssupporting
confidence: 90%
“…In present study, serum VLDL-C level rose significantly (P<0.05) in the third trimester of pregnancy in comparison to non-pregnant women, which is perhaps due to hypertriglyceridemia leading to enhanced entry of VLDL that carries endogenous triglyceride into circulation. These results are in accordance with Teichmann et al, (17) &Knopp et al, (18) and Potter and Netel, (19) whom reported that VLDL-C might rise up to 2.5 folds at term over the pre-pregnancy level.…”
Section: Total Lipid Profilesupporting
confidence: 91%
“…Obesity is associated with abnormalities of lipid metabolism [30]. Maternal non-estirified fatty acids can cross the placenta, and placental lipoprotein lipase hydrolyses triglycerides to fatty acids that can cross the placenta [31,32]. Thus, increased serum levels of maternal fatty acids and triglycerides may increase fatty acid transfer to the fetus.…”
Section: Discussionmentioning
confidence: 99%